2021
DOI: 10.3390/insects12100938
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length SMRT Transcriptome Sequencing and SSR Analysis of Bactrocera dorsalis (Hendel)

Abstract: Bactrocera dorsalis (Hendel), as one of the most notorious and destructive invasive agricultural pests in the world, causes damage to over 250 different types of fruits and vegetables throughout tropical and subtropical areas. PacBio single-molecule real-time (SMRT) sequencing was used to generate the full-length transcriptome data of B. dorsalis. A total of 40,319,890 subreads (76.6 Gb, clean reads) were generated, including 535,241 circular consensus sequences (CCSs) and 386,916 full-length non-concatemer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…3). This slight change in nucleotide composition in SUSBt and RESBt libraries compared to the others may be associated with the participation of TEs, since under stress these elements are more active [Pappalardo et al, 2021], and it is already known that in Lepidoptera microsatellites can be associated with TEs [Tay et al, 2010]. Ding et al [2017] observed that in the mono-and trinucleotide repeat types the composition was predominantly A/T, exactly as found in our study for A. gemmatalis.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…3). This slight change in nucleotide composition in SUSBt and RESBt libraries compared to the others may be associated with the participation of TEs, since under stress these elements are more active [Pappalardo et al, 2021], and it is already known that in Lepidoptera microsatellites can be associated with TEs [Tay et al, 2010]. Ding et al [2017] observed that in the mono-and trinucleotide repeat types the composition was predominantly A/T, exactly as found in our study for A. gemmatalis.…”
Section: Discussionsupporting
confidence: 86%
“…Ding et al [2017], in a vast study of SSRs in more than 130 insect genomes (deposited in a database), reported that the most abundant repeat motifs in insect genomes were di-(27.2%) and trinucleotide (22%) types. The trinucleotide-type repeats were also prominent in the transcriptomes of B. dorsalis (44.24%) [Ouyang et al, 2021] and D. citri, where 42.95% of the identified SSRs were of this type [Chen et al, 2014]. One of the explanations for this is that trinucleotide-type repeats would have possible stability in the protein-coding regions when compared to other types of repeat unit, rarely producing sliding mutations of the coding frame [Ouyang et al, 2021].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SMRT sequencing can provide a new comprehension of full-length sequences, greatly facilitating the transcriptome research of species lacking high-quality reference genomes and improving genome annotation. To date, only a few full-length transcriptome analyses have been reported in insects, such as Dendroctonus ponderosae ( Keeling et al, 2012 ), Chouioia cunea ( Pan et al, 2019 ), Sogatella furcifera ( Chen et al, 2020 ), Aphis aurantii ( Hong et al, 2020 ), Rhynchophorus ferrugineus ( Yang H et al, 2020 ), Bactrocera dorsalis ( Ouyang et al, 2021 ), Spodoptera frugiperda ( Yang et al, 2021 ), Diabrotica virgifera ( Zhao et al, 2021 ). There are still no published reference genomes for predatory stink bugs.…”
Section: Discussionmentioning
confidence: 99%